Adult Alveolar Soft Part Sarcoma of the Head and Neck: A Report of Two Cases and Literature Review. (23rd December 2014) - Mullins, Brandon T.; Hackman, Trevor
Abstract : Background . Alveolar soft part sarcomas (ASPS) of the head and neck are rare, aggressive soft-tissue malignancies. This study describes the clinical course and management of two patients presenting with ASPS in very rare head and neck locations, the larynx and parotid gland. Methods . We identified two patients presenting with ASPS of the head and neck and treated at the University of North Carolina. We compared our results to the literature from 1987 to 2013. Results . Patient ages at diagnosis were 27 and 39 with presenting symptoms of hoarseness and parotid swelling, respectively. Mean follow-up was 87 months. All patients received surgical resection and adjuvant radiotherapy. There were no recurrences or evidence of distant metastatic spread during the series. Disease-free survival time for the patients was 4 months and 168 months, respectively. Conclusions . Our study suggests that a combined-modality approach is important in the treatment of ASPS of the head and neck even in these rare locations. Continued research into new therapies is necessary to improve historically poor outcomes.